2022
DOI: 10.1111/dom.14693
|View full text |Cite
|
Sign up to set email alerts
|

The alpha‐7 nicotinic acetylcholine receptor agonist GTS‐21 engages the glucagon‐like peptide‐1 incretin hormone axis to lower levels of blood glucose in db/db mice

Abstract: Aim: To establish if alpha-7 nicotinic acetylcholine receptor (α7nAChR) agonist GTS-21 exerts a blood glucose-lowering action in db/db mice, and to test if this action requires coordinate α7nAChR and GLP-1 receptor (GLP-1R) stimulation by GTS-21 and endogenous GLP-1, respectively.Materials and Methods: Blood glucose levels were measured during an oral glucose tolerance test (OGTT) using db/db mice administered intraperitoneal GTS-21. Plasma GLP-1, peptide tyrosine tyrosine 1-36 (PYY1-36), glucose-dependent ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Wang et al showed that GTS-21 stimulates GLP-1 secretion in vitro from cultured L cells and raises circulating GLP-1 levels in vivo when administered to mice 22 . More recent studies by Meng et al show GTS-21 improves glycemic control in db/db mice and the glycemic effects require α7nAChR and GLP-1R stimulation 8 . These results provide evidence that GTS-21-mediated improvements in glycemic control are likely to contribute to the improvements in DN in the db/db model.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Wang et al showed that GTS-21 stimulates GLP-1 secretion in vitro from cultured L cells and raises circulating GLP-1 levels in vivo when administered to mice 22 . More recent studies by Meng et al show GTS-21 improves glycemic control in db/db mice and the glycemic effects require α7nAChR and GLP-1R stimulation 8 . These results provide evidence that GTS-21-mediated improvements in glycemic control are likely to contribute to the improvements in DN in the db/db model.…”
Section: Discussionmentioning
confidence: 98%
“…Understanding the genesis and treatment of DN is facilitated by the availability of hyperglycemic, obese, db/db mice in which there is a spontaneous point mutation in the leptin receptor (Lepr) leading to a loss of receptor signaling. These db/db mice are responsive to the α7 nicotinic acetylcholine receptor (α7nAChR) agonist GTS-21 which exerts a blood glucose-lowering effect 8 , and for this reason GTS-21 might be a previously unrecognized treatment for DN, as explored in the present study.…”
Section: Introductionmentioning
confidence: 99%
“…Our results that galantamine treatment reduced inflammatory cytokines (TNF-α, IL-6, HMGB-1), improved insulin resistance and glycemic control in the db/db mice are consistent with those of the clinical trial of galantamine in patients with metabolic syndrome. Of interest, previous work from our laboratory showed that treatment of db/db mice with α7nAChR agonists (GTS-21 or PNU-282987) increased GLP-1 secretion and improved oral glucose tolerance by a mechanism requiring an intact GLP-1 receptor 21 . This suggests that some, but perhaps not all galantamine’s effects (e.g., decreased food and weight loss) on glycemic control and inflammation are mediated by the α7nAChR and GLP-1 receptor at the tissue level.…”
Section: Discussionmentioning
confidence: 99%
“…Reflex activation of the vagal efferent in the brainstem reduces inflammation by activating the α7nAChR in peripheral tissues. A number of α7nAChR receptor agonists, including GTS-21, an α7 nicotinic acetylcholine receptor (α7nAChR) agonist can improve glycemic control and DN in the db/db mouse 21 23 .…”
Section: Introductionmentioning
confidence: 99%